On Love as Comedy: За љубовта како комедија - Zupančič, Alenka; Stojanovska, Natasha (Identities: Journal for Politics, Gender and Culture, 2003)
Author(s): Alenka Zupančič | Аленка Зупанчич Title (English): On Love as Comedy Title (Macedonian): За љубовта како комедија Translated by (English to Macedonian): Natasha Stojanovska | Наташа Стојановска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 2, No. 1 (Summer 2003) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 61-80 Page Count: 19 Citation (English): Alenka Zupančič, “On Love as Comedy,” Identities: Journal for Politics, Gender and Culture, Vol. 2, No. 1 (Summer 2003): 61-80. Citation (Macedonian): Аленка Зупанчич, „За љубовта како комедија“, превод од англиски Наташа Стојановска, Идентитети: списание за политика, род и култура, т. 2, бр. 1 (лето 2003): 61-80.